Burning sensation in the feet and glycosylated haemoglobin levels in Swedish- and non–Swedish-born primary healthcare patients - Taloyan, Marina (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• No statistically significant difference in reporting a burning sensation in the feet regarding HbA1c levels. • Non Swedish-born–patients had 70% higher odds of reporting a burning sensation in their feet. • Smoking habits might explain the differences in the odds in two regions of birth.